Posttranslational modification of tubulin by palmitoylation: I. In vivo and cell-free studies. - Caron, J M (1997)
It is well established that microtubules interact with intracellular membranes of eukaryotic cells. There is also evidence that tubulin, the major subunit of microtubules, associates directly with membranes. In many cases, this association between tubulin and membranes involves hydrophobic interactions. However, neither primary sequence nor known posttranslational modifications of tubulin can account for such an interaction. The goal of this study was to determine the molecular nature of hydrophobic interactions between tubulin and membranes. Specifically, I sought to identify a posttranslational modification of tubulin that is found in membrane proteins but not in cytoplasmic proteins. One such modification is the covalent attachment of the long chain fatty acid palmitate. The possibility that tubulin is a substrate for palmitoylation was investigated. First, I found that tubulin was palmitoylated in resting platelets and that the level of palmitoylation of tubulin decreased upon activation of platelets with thrombin. Second, to obtain quantities of palmitoylated tubulin required for protein structure analysis, a cell-free system for palmitoylation of tubulin was developed and characterized. The substrates for palmitoylation were nonpolymerized tubulin and tubulin in microtubules assembled with the slowly hydrolyzable GTP analogue guanylyl-(alpha, beta)-methylene-diphosphonate. However, tubulin in Taxol-assembled microtubules was not a substrate for palmitoylation. Likewise, palmitoylation of tubulin in the cell-free system was specifically inhibited by the antimicrotubule drugs Colcemid, podophyllotoxin, nocodazole, and vinblastine. These experiments identify a previously unknown posttranslational modification of tubulin that can account for at least one type of hydrophobic interaction with intracellular membranes.